COVID-19 PANDEMIC: INFLUENCE OF RELATIONSHIP STATUS ON ANXIETY AND DEPRESSION IN ADULTHOOD POPULATION OF NORTH MACEDONIA - Beluli Luma, Nita (International Scientific Journal Vision, 2021)
he aim of this study was to assess the associations between relationship status and mental well-being during this time when the world is facing with the greatest bio-psycho-social threat known as coronavirus COVID-19 pandemic. Regarding the mental health we have taken two mental issues which have shown to be most common as consequences of the impact of the safety measures and social distance limitations we have been obliged to respect in order to prevent further spread of the infectious disease, which are: depression and anxiety. Another purpose of our research is to identify whether age stage and gender, moderated these associations. We wanted to understand and examine the impact of relationship status on levels of anxiety, and depression during the coronavirus (COVID-19) pandemic to identify relationship status groups, divided by their age groups and gender, who are at greater risk of mental health difficulties. Relationship status during the COVID-19 pandemic has an influence on the mental health of individuals. Our findings highlight relationship groups at risk of mental health problems during the pandemic and for whom treatments and mitigation should be targeted. Compared to marriage, being engaged or being divorced/widowed were associated with depressive and anxious symptoms at men and women. Early adult males have shown greater levels of depression than all other age stages in adulthood, even exceeding females in all categories as well. Men are more depressed than women in all age stages of adulthood when compared. While late adult woman are the most anxious between the groups and when compared to men as well.